Mechanochemical-hydrothermal synthesis of layered lithium titanate hydrate nanotubes at room temperature and their conversion to Li4Ti5O12. (June 2017) - Suzuki, Shinji; Kozawa, Takahiro; Murakami, Takeshi; Naito, Makio
Graphical abstract: The present study demonstrates a simple mechanochemical-hydrothermal approach to synthesize Li1.81 H0.19 Ti2 O5 · x H2 O nanotubes from LiOH, TiO2, and water. Highlights: A breakthrough of mechanochemical-hydrothermal method is demonstrated. Li1.81 H0.19 Ti2 O5 · x H2 O (LHTO) was synthesized by a planetary ball milling in water. LHTO nanotubes were formed at room temperature from LiOH, TiO2, and water. The formation of LHTO nanosheets and the shape change to nanotube were observed. The anode properties of LTO nanotubes for Li-ion batteries were evaluated. Abstract: Mechanochemical-hydrothermal synthesis is a low-cost and efficient method to prepare functional particles, due to the local high-pressure and high-temperature reaction fields generated during the process. Here, mechanochemical-hydrothermal synthesis of layered lithium titanate hydrate, Li1.81 H0.19 Ti2 O5 · x H2 O (LHTO), using a planetary ball mill is demonstrated. By planetary ball milling of LiOH and TiO2 with water at room temperature, LHTO nanotubes with lengths over 300 nm were synthesized. The synthesized LHTO nanotubes were transformed to Li4 Ti5 O12 (LTO), which is a common anode material for Li-ion batteries, via thermal treatment while maintaining the nanotube morphology. The anode properties of the thermally prepared LTO nanotubes exhibited a first discharge capacity of 160 mAh/g at a rate of 0.1 C, even though residual TiO2 and contamination from ZrO2 milling balls were observed as product impurities. The reduction of impurities in the product after mechanochemical-hydrothermal synthesis is important to improve material performances.